Performance evaluation of the structural system using the pushover analysis method on the DPRD Bojonegoro building based on SAP2000 - Sujiat, Sujiat; Faridatun Nisa, Firna (Edumaspul: Jurnal Pendidikan, 2025)
ndonesia is an earthquake-prone country because it is located at the meeting point of three very active world tectonic plates. The movement of the earth's plates is the main factor in the occurrence of earthquakes, which have great potential to cause damage to building structures. So that by designing earthquake-resistant buildings, this can be minimized. In addition, in the implementation of a construction project, the foundation also has a very important role. The foundation must be able to withstand the load so as not to exceed the predetermined safe limit. The purpose of this final project is to determine the structural performance level of the Bojonegoro DPRD building using the pushover analysis method that refers to the ATC-40 criteria and to determine the bearing capacity of the foundation. The results of this analysis show that the behavior of the structure begins with the appearance of plastic joints first in the beam then followed by the column. Based on the results of the capacity spectrum analysis, the total maximum deviation in the X direction is 0.017 mm and the maximum inelastic deviation is 0.015 mm. in the Y direction, the total maximum deviation is 0.013 mm and the maximum inelastic deviation is 0.011 mm. referring to ATC (1996), the performance of the structure is in the Damage Control (DC) category. And based on the results of the analysis of the bearing capacity of the pile foundation based on N-SPT with the friction method, it shows that starting from a depth of 12 m, the bearing capacity is sufficient. At a depth of 12 m, the allowable bearing capacity is 34.515 tons. At a depth of 13 m, the allowable bearing capacity is 37.818 tons. And at a depth of 14 m, the permitted bearing capacity is 44,513 tons. At a depth of 12 - 14 m, it is able to withstand a load of 34 tons